Pengaruh Penerapan Media Pembelajaran Monopoli Petualangan Nusantara terhadap Motivasi Belajar Siswa dalam Mata Pelajaran IPS Kelas V di Sekolah Dasar Negeri Timbang - Nurul Ivani; Agatha Kristi Pramudika Sari (Edukhasi: Jurnal Inovasi Pendidikan, 2023)
This study aims to: (1) To find out the application of archipelago adventure monopoly learning media to students' learning motivation in social studies subjects in class V at SD Negeri Timbang. (2) To find out the effectiveness of the application of archipelago adventure monopoly learning media on student learning motivation in social studies class V at SD Negeri Timbang. (3) To find out the effect of the application of archipelago adventure monopoly learning media on students' learning motivation in social studies class V at SD Negeri Timbang. This study uses a Quasi Experimental Design research type. The research design used is True experimental design. This design is a type of research design that belongs to the Posttest-Only Control Design approach. In this study, the population was all fifth grade students at SD Negeri Timbang, Cigandamekar sub-district, while for the sample, there were 21 class Va students and 22 class Vb students. The average posttest result in the control class (Va) was 69. And the average score in the experiment class 86 which experienced an increase of 12.05. Based on the results of calculations using SPSS 29.00, it is known that the value of Tcount (3.111) > Ttable (2.073) and a significance value of 0.003 <0.05, it can be concluded that the variable influence of Monopoly Media Adventures of the Archipelago (X) affects students' learning motivation in social studies class V at SD Negeri Tambang Cigandamekar, Kuningan.